2021
DOI: 10.1016/j.mcpro.2021.100151
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modifications Switch Modulatory Activities of Urinary Proteins From Inhibiting to Promoting Calcium Oxalate Crystallization, Growth, and Aggregation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Crystallization assay was employed to validate the effects of CNB on COM crystallization using lysozyme as the negative control. The results demonstrated that total urinary proteins (TUPs) from healthy subjects, that are known to strongly inhibit COM stone formation [17] , markedly reduced COM crystal size, number and abundance comparing with blank and negative controls ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Crystallization assay was employed to validate the effects of CNB on COM crystallization using lysozyme as the negative control. The results demonstrated that total urinary proteins (TUPs) from healthy subjects, that are known to strongly inhibit COM stone formation [17] , markedly reduced COM crystal size, number and abundance comparing with blank and negative controls ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 95%
“…TUPs were prepared from healthy subjects as described previously [17] . The study protocol met the standard guidelines (Declaration of Helsinki, Belmont Report, and ICH Good Clinical Practice) and was approved by Siriraj Institutional Review Board (approval no.…”
Section: Methodsmentioning
confidence: 99%
“…The results from crystallization assay indicated that succinic, salicyluric acid and gentisic acid could decrease the size and number of the crystals, which was consistent with previous studies of inhibitor for COM crystallization. 43 , 44 During crystallization, succinic, salicyluric acid and gentisic acid can shift COM towards COD crystallization, which may confer a therapeutic effect as COD has lower affinity to epithelial cell membrane molecules and may thereby reduce intratubular retention. 11 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were measured using Bio-Rad protein assay (Bio-Rad; Milano, Italy) based on Bradford’s method. An equal amount (30 µg) of total proteins from each sample was subjected to in-solution tryptic digestion as described previously [18] , [19] . The digested peptides were then analyzed by nanoLC-ESI-LTQ-Orbitrap MS/MS as previously reported [20] , [21] .…”
Section: Methodsmentioning
confidence: 99%